NEW SYSTEMATIC APPROACHES IN TREATMENT OF COEXISTENT DAMAGES OF ABDOMEN AND EXTREMITIES - Ibrahimov, F.I. (World of Medicine and Biology, 2022)
A retrospective and prospective analysis of the data of 1033 patients with severe combined trauma who were treated in 2009–2015 at the Baku City Clinical Hospital No.3 was carried out. For the purpose of comparative analysis of treatment methods, patients were divided into two groups. In total, there were 216 patients with combined injuries to remove icons in the words of the abdomen and limbs, 171 of them were included in the main group, 45 in the comparative group. The scales of injury severity (Abbreviated Injury Scale and Injury Severity Scale) assessed the severity of injuries of patients in the main group; they were assisted taking into account the principle of “damage control”. In 52.1 % of patients of the main group with severe combined trauma of the abdomen and extremities, who were treated taking into, account the principle of “damage control” and the use of programmed multi-stage surgical tactics, with subcompensation of traumatic disease. The mortality rate was 16 %, in the comparative group – 44.4 %, with decompensation – 51.6 and 89.7 %, respectively. The results of using multi-stage surgical tactics with severe combined abdominal and limb injury demonstrate its obvious advantages.
Keywords: severe combined trauma; fractures of the tubular bones of the limbs; concept of “damage control”; tactics of programmed multi-stage surgical treatment; surgical activity; lethality